Structure, Expression, and Evolution of Guinea Pig Serum Amyloid P Component and C-Reactive Protein - Rubio, Nadina; Sharp, Paul M.; Rits, Miriam; Zahedi, Kamyar; Whitehead, Alexander S. (Journal of biochemistry (Tokyo), 1993)
The structure and expression of the pentraxins, serum amyloid P component (SAP), and C-reactive protein (CRP), have been investigated in the guinea pig. Northern blot analysis of hepatic RNA from animals in which acute inflammation had been induced by intraperitoneal injection of thioglycollate established that neither SAP or CRP is a major acute phase reactant in the guinea pig. Genomic clones of SAP and CRP were isolated and sequenced, and the gene and the derived protein sequences were compared with other mammalian homologues. Both genes have organizations typical of the pentraxin genes of other species, but some differences were defined in the regions that potentially determine the capacity of the pentraxin gene to be induced during acute inflammation. Nucleotide substitutions in coding regions have occurred at similar rates in the two pentraxin genes. Nonsynonymous substitution rates indicate that SAP and CRP are subject to similar, relatively low levels of constraint; at the amino acid sequence level the rate of evolution is approximately two replacements per site per 109 years. An estimate of the phylogenetic elationship among the pentraxin genes suggests that SAP and CRP arose as the result of a gene duplication event that occurred very early in mammalian evolution, but subsequent to the divergence of the reptilian ancestors of the mammalian and avian lineages. This raises doubts about the identity of proteins from fish, which have been previously characterized as CRP and SAP.